Possibility of Secondary Sub-micron Aerosol Mass Concentrations Forecasting: A Case Study Toward the Possibility of A Future Nowcasting Approach - Casazza, Marco (Journal of Environmental Accounting and Management, 2026)
Particulate Matter (PM) pollution represents a global concern, due to its adverse effect both on environment and on human health. European Environmental Protection Agency data reveal that one of the most exposed regions is Northern Italy. The attention has been focused on a metropolitan city within this area, Torino (NW Italy), and studied the relation between sub-micron particles and their precursor gases under real atmospheric conditions, considering that fine particles have the most relevant adverse health effects. A photolytic computation model developed using an environmental chamber has been adapted and tested for real environmental conditions. The obtained algorithm can constitute the basic building-block for an effective PM1 nowcasting method. Testing it through the use of 2008-2011 summertime data (during the summer the photolytic activity is greater), selected considering only the days with stable fine weather conditions, we found that there is a strong stable dependence between the concentrations of sub-micron particles and its precursor gases, NO in particular. This fact will allow to calculate separately the dependence of PM1 mass concentration values (that represent 65% of PM10) on generation, respect to transport and scavenging phenomena. Finally, this result makes clear that an active policy on NO emission reduction should have effects also on PM pollution in the atmosphere.